Percutaneous Ethanol Injection vs Reoperation for Locally Recurrent Papillary Thyroid Cancer - Patricia, Patricia; Josephine, Josephine (The Indonesian Journal of General Medicine, 2024)
Background: The literature presents a compelling case for the use of percutaneous ethanol injection therapy (PEIT) as a treatment modality for locally recurrent papillary thyroid cancer, particularly when compared to traditional surgical reoperation. The studies reviewed highlight the evolution of PEIT from its initial applications in benign conditions to its potential in managing malignancies. Literature Review: Overall, the literature indicates a growing consensus on the viability of PEIT as an alternative to surgical reoperation for locally recurrent papillary thyroid cancer, particularly for patients who may not tolerate more invasive procedures. The progression from initial applications in benign lesions to considerations for complex malignancies underscores the adaptability and potential of PEIT in clinical practice. Conclusion: The collective insights from these articles support the notion that PEIT could serve as a viable alternative to surgical reoperation for patients with locally recurrent papillary thyroid cancer. The evidence suggests that PEIT not only maintains a favorable safety profile but also offers significant therapeutic benefits, particularly for patients who may be at higher risk for surgical complications. Further research comparing the long-term outcomes of PEIT and surgical reoperation is warranted to solidify its role in clinical practice.